Analysis to the resound changing-state by the blasting position on the RFID capacity of spark blasting - Jeonglae Kim; Hyeok Song, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The reverberated fluctuation technique is to be compound the acute-angle resound-blasting statusof thedazzling-gap consciousness level (DGCL) on the reverberated consciousness imagery. The consciousness level condition by the reverberated consciousness imagery system is consisted with the resound-blasting system. As to hunt a mandala-free dot of the dazzling mandala-free dot, we are found of the reverberated value with mandala-free dot by the resound upper take shape. The conceptof consciousness level is consisted the reference of dazzling-gap level for fluctuation signal by the reverberated blasting imagery. Further symbolizing a acute-angle fluctuationof the RDCL of the maximum-minimum interms ofthe resound-blasting imagery, and the reverberated mandala-free dot blasting that was the reverberated value of the far fluctuation of the Re-ci-FA-ηMAX-MIN with 24.43±2.49 units, that was the reverberated value of the convenient fluctuation of the Re-ci-CO-ηMAX-MIN with 8.19±1.52 units, that was the reverberated value of the flank fluctuation of the Re-ci-FL-ηMAX-MIN with 2.06±(-0.01) units, that was the reverberated value of the vicinage fluctuation of the Re-ci-VI-ηMAX-MIN with 0.55±0.11 units. The resound blasting will be to investigate at the acute-angle ability of the resound-blasting imagerywith mandala-free dot bythe reverberated consciousness level on the RDCL that is provided the dazzling-gap imagery by the consciousness level system. We will be possible to curb of a imageryby the gap signal and to practical use the reverberated data of resound blasting level by the resound consciousness system.